Pilkada Dalam Pandemic: Bagaimana Warga Negara Memaknai Demokrasi Indonesia - Romdani, Lisda Nurul; Suryadi, Karim (Department of Pancasila and Civic Education, Universitas Negeri Medan, 2021)
AbstractLocal election in 2020 is a form of democracy for the Indonesian people, with this aim, namely to see how citizens interpret the concept of democracy in Indonesia during the elections held during the Pandemic. This research was conducted using the method of literature study (library research) or research with literature studies, namely research data and information from scientific journals and books as well as research results. Such is the data process obtained that the holding of regional head elections in a Pandemic reaps pros and cons. The media is a public space that is used by citizens in realizing their participation, and the manifestation of a citizen's democratic attitude can be seen from his role through the public space in his decision-making process. Thus, the media as a means of political discussion in the community, this can be said as the meaning of democracy that can be seen by every individual in the practice of citizenship.————- AbstrakPemilihan Kepala Daerah serentak yang diselenggarakan pada tahun 2020 merupakan wujud demokrasi bagi bangsa Indonesia, tujuan penulisan ini yaitu untuk mengetahui bagaimana warga negara memaknai konsep demokrasi di Indonesia saat pilkada yang dilaksanakan saat Pandemic. Penelitian ini dilakukan dengan metode studi literatur (library research) atau penelitian dengan studi pustaka, yaitu pengumpulan data dan informasi dari jurnal ilmiah dan buku serta hasil penelitian. Demikian proses data yang didapatkan bahwa penyelenggaraan pemilihan kepala daerah dalam Pandemic menuai pro dan kontra. Media menjadi ruang public yang digunakan warga negara dalam mewujudkan partisipasinya, dan perwujudan sikap demokratis seorang warga negara dapat dilihat dari peran dirinya melalui ruang public dalam proses pengambilan keputusannya. Demikian, media sebagai sarana diskusi politik di kalangan masyarakat, hal ini dapat dikatakan sebagai makna demokrasi yang dapat dilihat setiap individu dalam praktek kewarganegaraan.